Primary Yolk Sac Tumor in the Cerebellar Hemisphere: A Case Report and Literature Review of the Rare Tumor - Wu, Na; Chen, Qiang; Chen, Meng; Ning, Jinbo; Peng, Shulei; Zhang, Taotao; Zhong, Wen; Duan, Song; Cheng, Chongjie; Xie, Yimin (Frontiers in Oncology, 2021)
Primary intracranial yolk sac tumor (YST), also endodermal sinus tumor (EST), is a quite rare type of brain tumor. YST is one of rare malignant germ cell tumors (GCTs) .Here, we present a case, review the literature，and propose a treatment strategy for this rare tumor. Here, a 6-year-old boy initially manifested symptoms of dizziness and vomiting. Computed tomography (CT) and magnetic resonance imaging (MRI) revealed a large irregularly circular tumor in the cerebellar hemisphere. The tumor was subtotally resected by microsurgery via the left suboccipital approach. Immunohistochemical staining was positive for alpha-fetoprotein (AFP) and the Ki-67 proliferation index was high (60%), indicating germ cell tumor. During 3 months of follow-up, the tumor did not recur, and the patient suffered no complications. The diagnosis of YST requires a combination of clinical presentation, neuroimaging, and pathology. The ideal therapy for YST is gross total resection (GTR). However, GTR is usually difficult and carries a high risk of postoperative complications because of the tumor location. This reported case indicates that subtotal resection can be a good treatment strategy for YST.